The Role of Root Morphology and Pulling Direction in Pullout Resistance of Alfalfa Roots - Yang, Qihong; Zhang, Chaobo; Liu, Pengchong; Jiang, Jing (Frontiers in Plant Science, 2021)
There is a growing consensus on soil conservation by mechanics of plant root system. In order to further study how root system exerts its mechanical properties during soil reinforcing process and which morphological indicator is suitable for reflecting pullout resistance, in-situ vertical pullout test (VPT) and 45° oblique pullout test (OPT) were performed on alfalfa (Medicago sativa L.) roots in the loess area. The results showed that the failure mode of alfalfa roots was pulling out in this study. The peak pullout resistance of the roots increased with root diameter, root length and root surface area, and power law relationships were observed between the pullout resistance and the morphological indices: root diameter, root length and root surface area. The maximum grey relational degree of the morphological indices was 0.841 (VPT) and 0.849 (OPT) for root surface area, suggesting that root surface area was a more significant root morphological index affecting root pullout resistance than root diameter and root length, and was more suitable for characterizing the difference in peak pullout resistance of roots with different size. The index could be used to validate the methods for predicting root pullout capacity. The value of peak pullout resistance was 17.2±2.3 N in VPT test and 28.2±3.8 N (mean ± SE) in OPT test, and a significant difference was observed between the two tests, which showed that the pulling direction significantly affected the peak pullout resistance of alfalfa roots. Vertical pullout test, giving the safety margin, was suggested to determine root pullout resistance for estimate of root reinforcement.